Microwave Drying of Hevea Rubber Latex and Total Solid Content (TSC) Determination - Khalid, Kaida; Abdul Wahab, Zaidan; Kasmani, Abdul Rahman (1988)
This paper deals with the microwave drying of the hevea rubber latex. It outlines the theoretical and experimental aspects on the effect of sample weight (5 gm to 15 gm), microwave power levels (3W/ cm3 to 10.6W/cm3) and initial TSC (25% to 60%) to the drying rate and final drying time. A series of drying curves (mass versus drying times) was generated and optimum conditions for drying were determined. A close relationship between theory and experiment has been found. The drying rate and final drying time for 5 to 15 gm samples with TSC = 39.2% at 9.3 W/cm 3 is approximately 0.07 gm/sec and 4 minutes respectively. A large amount of sample > 20 gm is avoided to prevent any explosion and sputtering of the sample during drying process. It is suggested that the optimal mass and power level are 10 gm and 9.3 W/cm 3 respectively. The experimental results clearly showed that micro were drying is very efficient for drying of fresh hevea latex as the conventional drying method needs 1 to 2 hours.